Cloud Computing Integration in the Digital Transformation of MSMEs: A Case Study on the Retail Sector - Nila Natalia; Errysa Subekthi; Febri Dolis Herdiani; Foezi Arisandi SJ (Technologia Journal, 2025)
This study aims to analyze the role of cloud computing integration in supporting the digital transformation process of Micro, Small, and Medium Enterprises (MSMEs) in the retail sector in Indonesia. Digital transformation has become a strategic necessity in facing the dynamics of global competition and changes in technology-based consumer behavior. This study uses a qualitative method with a case study approach on several retail MSMEs that have adopted cloud computing services. Data were obtained through in-depth interviews, field observations, and documentation, then analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of cloud computing can improve operational efficiency, strengthen data management, and accelerate the decision-making process based on real-time information. MSMEs that adopt this technology experience a reduction in IT infrastructure costs of up to 40% and an increase in employee productivity of up to 30%. However, challenges remain such as limited digital literacy, uneven internet infrastructure, and concerns about data security. This study confirms that cloud computing functions not only as a technological solution, but also as a catalyst for changing work culture and business management systems towards sustainable digitalization.